2011
DOI: 10.1134/s1063782611070104
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal conductivity of layered charge-ordered crystals in a high quantizing magnetic field

Abstract: The longitudinal Seebeck coefficient of the charge-ordered layered crystals in a strong quantizing magnetic field normal to layers plane has been determined.The conditions whereby charge ordering parameter and chemical potential of charge carriers are the oscillating functions of the magnetic field induction are considered. The longitudinal Seebeck coefficient has been calculated for two models of the relaxation time: i) constant relaxation time and ii) the relaxation time proportional to the longitudinal velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…On the other hand, in the previous works, the author showed that, if the behavior of charge carriers in the direction perpendicular to the layers is studied, the layered-structure effects can be well pronounced in the case of a closed FS as well [12] or if the topological transition from the open FS to a closed one takes place [13].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, in the previous works, the author showed that, if the behavior of charge carriers in the direction perpendicular to the layers is studied, the layered-structure effects can be well pronounced in the case of a closed FS as well [12] or if the topological transition from the open FS to a closed one takes place [13].…”
Section: Introductionmentioning
confidence: 94%
“…For the calculation of the power factor, we also need an expression for the relaxation time τ 0 . For any γ 0 , this quantity can be determined in the same way as in works [12,13], namely, by the formula…”
Section: Calculation Of the Power Factor For A Layered Crystal And Di...mentioning
confidence: 99%